Developing a Predictive Metric to Assess School Viability - James, John T.; Tichy, Karen L.; Collins, Alan; Schwob, John (Catholic Education: A Journal of Inquiry and Practice, 2008)
This article examines a wide range of parish school indicators that can be used to predict long-term viability.